Some clinical and humoral aspects of liver failure in children and adolescents - Pablo Antonio Hernández Dinza; Elizabeth Aurora Cabrera Cabrales; Rosario Guerra Cosme; Marlen Quesada Castillo; Aloima Reifes Martén (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The acute liver failure is an entity of multifactorial origin that is presented in previously healthy children and has direct repercussion in the synthesis, clotting and purification functions.  Objective: To characterize children with acute liver failure according to clinical and humoral variables.  Methods: A retrospective and descriptive study of 19 patients with diagnosis of acute liver failure was carried out, they were assisted in the Pediatric Intensive Cares Unit of the   Southern Children Hospital in Santiago de Cuba, from April, 1998 to the same month in 2018, for which theoretical and statistical methods were used.  Results: In the case material there was a prevalence of the female sex (57.9 %), the mean age was 5 years and the infection constituted the most common cause (73.7 %). The hepatotropic virus as the hepatitis A were the most frequent. The complications of more observance were the respiratory alkalosis (63.1 %), the multiorganic dysfunction (42.1 %) and the liver brain disease (31.6 %). The low figures of cholesterol and the prothrombin time higher than 20 seconds were associated with a greater lethality.   Conclusions: In the patients younger than one year the non hepatotropic virus constituted the most frequent origin in this disease.